Investigating the flow of information in a surface iron ore mining operation - Loeto Levious, Sekwati (University of the Witwatersrand, Johannesburg, 2024)
As one of the most advanced iron ore mining operations Sishen Mine has many processes and systems. As an Anglo-American flagship operation, Sishen Mine has implemented many new systems and processes to improve its effectiveness and efficiency. This increased the number of resources (equipment, infrastructure and people). Over the last 10 years, Sishen Mine has doubled the number of employees and resources. The increase in resources, especially employees, processes and systems, has made it difficult for information to flow across the mine. The research aimed to determine the factors that contribute to the issue of gaps in the flow of information. A literature review was done on the current structure of information flow at Sishen Mine and some key discoveries were made. It was found that in a mining operation, there are three main core departments: engineering, mining operation and technical service. These departments depend on each other as the mine value chain is interlinked. The importance of information flow “enabling organisation structure”, communication structure and systems that will be able to enable efficient communication was emphasised. Ten participants across the mine were interviewed to get more details on the research question. The participants had many different views on the research question and as a result, a variety of ideas were discussed. Some of the ideas were linked to what was already discovered during the literature review. Unintegration of KPIs, technical and communication systems, and processes were among the highest contributors to miscommunication between individuals, sections and departments. The mine communication structure was also found not to be centralised and as a result, information flows are divergent. The lack of an integrative culture between individuals resulted in certain professionals having a silo mentality and thus being reluctant to share information. It is envisaged that the Centralised and Integrative System (CAIS) will be able to close the existing gaps in the information flow by focusing on centralising and integrating all critical systems and processes within Sishen Mine.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Mining; Information flow; iron ore; SDG-17: Partnerships for the goals